Consumer Purchase Intention toward BYD Electric Vehicles: The Influence of Price, Quality, and Brand Image - Ibnu Hajar , Al Hafidh; Widayati, Catur (Journal Economic Business Innovation, 2026)
Purpose: The purpose of this paper is to investigate the effects of price, product quality and brand image on consumer purchase intention for electric cars in an emerging market. Method: An empirical study was generated to measure the direct effects of latent constructs by structural modeling that includes consumer perception data. Findings: The research findings reveal that price, product quality and brand image also have a significant and positive influence on purchase intention. Of these antecedent brand image is found to be the most influential predictor, reflecting that symbolic and trust perceptions are primary in influencing consumer's chosen action. Price perception affects purchase intention positively through perceived value and product quality enhances confidence in technological performance and reliability. The three variables combined account for a large portion of variance in purchase intent, demonstrating the multidimensional character of EV adoption. Novelty: This paper combines perceived value theory with brand signaling and empirically investigates the relative impacts of functional and symbolic factors on intention to purchase electric vehicles in an emerging-country context. Implications: The paper also implies that manufactures may need to place brand-building strategies as strategic priority together with cost-based competition and quality improvement, and policymakers are recommended to initiate the projects of confidence building for consumer concerning electric vehicle brands.